Flood hazard analysis in small catchments: Comparison of hydrological and hydrodynamic approaches by the use of direct rainfall. Issue 4 (29th June 2020) - David, Amrei; Schmalz, Britta
Abstract: The classical 'decoupled' approach for fluvial flooding makes use of hydrographs as input boundary conditions. The catchment hydrology is determined by empirical semi‐distributed rainfall–runoff models, the flood processes by the use of hydrodynamic models. However, for urban floods, the distributed rainfall is set directly as input ('direct rainfall modelling' – DRM) to the elements of the 2D model. This 'integrated approach' aims to include hydrological and hydraulic processes in one single model. In this study, both modelling approaches are applied and evaluated for their suitability to determine flood hazards in small, rural catchments. The resulting flood maps and flow hydrographs are compared for selected rainfall–runoff events in a catchment located in Central Germany. In the first approach, the hydrological model (HEC‐HMS) from the Hydrologic Engineering Center (HEC) is used to generate the inflow boundary hydrographs for the 2D model (HEC‐RAS), which is then used to simulate the flow variables for the river network and its floodplains. For the second approach, the DRM is applied over the whole catchment by the use of HEC‐RAS. Special focus is given for the integrated approach to the difficulties occurring during the model optimisation and calibration. The comparison of the results and modelling processes of both approaches give insights into the advantages, disadvantages and difficulties or limitations of each presented approach.